Advanced endometriosis with infiltration of urinary bladder in young women - Malinowski, Andrzej; Szram, Krzysztof; Cieślak, Jarosław; Blewniewska, Grażyna; Augustyniak, Tomasz; Pawłowski, Tadeusz (Menopause Review/Przegląd Menopauzalny, 2004)
We described a case of endometriosis in 26 years old woman who complains from over half a year lasting disuric symptoms, which has not subjected conservative therapy. In cystosocopic examination there were no abnormalities detected. During operation we found and removed a solid endometic infiltration of the urinary bladder wall and cystoplasty was performed.